Preoperative temporal bone HRCT and intra-operative findings in middle ear cholesteatoma: a comparative study - Dashottar, Sunita; Bucha, Atul; Sinha, Shilpa; Nema, Devender (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2018)
Background: Middle ear cholesteatoma is a potentially dangerous condition owing to the varied extra-cranial as well as intra-cranial complications, it can be associated with. Clinical suspicion and otologic examination sufficiently identifies the pathology but its entire extent and spread is delineated by HRCT examination only, which is presently the ‘Gold Standard’. In this study we tried evaluate the efficacy of HRCT temporal bone in depiction of extent of pathology in cases of cholesteatoma of middle ear and we tried to verify the findings on HRCT imaging with intra-op findings. Methods: A prospective observational study comprising of 50 patients suspected of middle ear cholesteatoma was carried out at a tertiary care hospital in Lucknow, India. Pre-op evaluation with bilateral temporal bone HRCT imaging followed by suitable surgery was performed. Important pre-operative HRCT and intra-operative surgical findings were correlated for statistical significance. Results: Mesotympanum involvement (96%) was the most common HRCT finding as far as location and extent were concerned and incus erosion (70%) was the most common bony complication. A high sensitivity and specificity (82% -100%) of HRCT was found in detection of Erosion of scutum, tegmen tympani and incus. For findings such as stapes erosion and facial canal erosion on HRCT, a sensitivity of 68.4% and 50% respectively was found when compared to intra-op findings. Conclusions: HRCT temporal bone is a useful tool in pre-operative delineation of the extent of cholesteatoma and the recognition of its manifestations and complications. It can help the operating surgeon in appropriate surgical planning.